Efektivitas Bimbingan Perkawinan Pra Nikah untuk Mencapai Keluarga Sakinah di Kec. Silangkitang (International Forum of Researchers and Lecturers, 2025)
Marriage or marriage is a contract that legitimizes association and limits the rights and obligations between a man and a woman who are not mahram. To achieve marriage, pre-marital guidance is provided for prospective brides and grooms which is the order of the Ministry of Religion through the KUA in the District, one of which is the KUA in Silangkitang District. Therefore, one of the pre-marital guidance aims to provide a good and correct understanding, so that Muslim families will be able to realize a sakinah mawaddah warahmah family. So is pre-marital guidance effective in realizing this at the KUA Silangkitang for prospective brides and grooms there, this study will discuss this. From the background above, the author focuses on two problem formulations, namely (1) How is the effectiveness of the law on pre-marital guidance according to the KUA Silangkitang District? (2) How is the effectiveness of the law on pre-marital guidance according to prospective brides and grooms at the KUA Silangkitang District? The type of research conducted by the author is field research using qualitative types. The data collection techniques for this study are observation, interviews and documentation. Meanwhile, for the research analysis, the theory of Miles and Hubermen is used, namely data reduction, data display, and drawing conclusions or verification. The effectiveness of the law on premarital guidance according to the KUA of Silangkitang District has been effective in five aspects. Regarding the effectiveness of the law on premarital guidance according to prospective brides and grooms at the KUA of Silangkitang District, it has been effective in four aspects, (legal factors, law enforcement factors, factors of facilities or facilities that support law enforcement, community factors). What has not been fulfilled is the aspect of the culture of the community or the culture of the community has not been effective because some of the bride and groom do not understand premarital guidance.